AI in Indonesian Accounting Practices: Readiness, Ethical Challenges, and Financial Reporting Quality - Firdaus Indrajaya Tuharea; Dini Ayu Pramitasari; Anisaul Hasanah; Bustanul Ulum (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study evaluates Indonesian accounting institutions' readiness for AI adoption, identifies key ethical issues, and assesses AI's impact on reporting quality. Employing a mixed-methods approach, the study gathered quantitative data via a survey of 120 professional accountants and financial managers, alongside qualitative insights from in-depth interviews with 10 key informants across academia, practice, and regulatory bodies. Data were processed using descriptive statistics and inductive thematic analysis. Findings reveal a moderate level of institutional readiness. While technological infrastructure and managerial support are strong, significant weaknesses exist in internal policy formulation and digital ethics training. Major ethical challenges include system accountability, algorithmic bias, and process transparency. Regarding reporting quality, AI enhances information relevance, reliability, and timeliness, though understandability remains reliant on human interpretation.